Introduction to Data Mining with case studies - G.K. Gupta (Prentice-Hall of India, 2006)
The field of data mining provides techniques for automated discovery of most valuable information from the accumulated data of computerized operations of enterprises. This book offers a clear and comprehensive introduction to both data mining theory and practice. It is written primarily as a textbook for students of computer science, management, computer applications, and information technology. The book ensures that students are exposed to all major data mining techniques without the mathematical rigour that one would prefer to use. To enhance the understanding of the concepts introduced, and to show how the techniques described in the book are used in practice, each chapter is followed by one or two case studies that have been published in scholarly journals. Studying case studies will provide the reader with a lot of insight into data mining. The book also provides many examples, end-of-chapter exercises, and a good list of references and Web resources especially those which are easy to understand and useful for students.